2014
DOI: 10.1177/1065912914525861
|View full text |Cite
|
Sign up to set email alerts
|

Who Takes the Parliamentary Floor? The Role of Gender in Speech-making in the SwedishRiksdag

Abstract: Legislative speeches are an important instrument for parties and members of parliament (MPs) to signal their positions and priorities. This raises the question of who speaks when. We evaluate whether a MP's presence on the floor depends on his or her gender. We hypothesize that female MPs give in general less speeches in parliament and that this pattern results from debates dealing with "harder" policy issues. Our expectations are supported when analyzing a new data set containing information on the number and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 51 publications
(78 reference statements)
8
128
0
21
Order By: Relevance
“…For example, Wängnerud (2015: 69) notes in reference to a question in the Swedish Parliamentary Survey that women are significantly less satisfied than men concerning their working conditions in party groups. Men also speak more than women, and on different issues, in parliamentary chamber debates (Bäck, Debus, and Müller, 2014). The male and female members of the current parliament are rather similar in respect to their observable characteristics.…”
Section: The Swedish Casementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wängnerud (2015: 69) notes in reference to a question in the Swedish Parliamentary Survey that women are significantly less satisfied than men concerning their working conditions in party groups. Men also speak more than women, and on different issues, in parliamentary chamber debates (Bäck, Debus, and Müller, 2014). The male and female members of the current parliament are rather similar in respect to their observable characteristics.…”
Section: The Swedish Casementioning
confidence: 99%
“…Previous research has established that Swedish female MPs speak less in parliamentary debates than their male colleagues (Bäck, Debus, and Müller, 2014). We go beyond formal speeches in parliamentary debate in this study, focusing instead on informal aspects of the debate space, namely, MPs' self-reported debate participation in their legislative committee and parliamentary party group.…”
Section: Debate Participationmentioning
confidence: 99%
“…We consider how governing parties' commitment (and ability) to change policy interacts with individual ideology to generate electoral incentives for MPs to craft an image of independence through rebellion. In doing so, we contribute to the growing literature on representation and electoral signalling through legislative votes and speech (Bäck, Debus and Müller 2014;Herzog and Benoit 2015;Proksch and Slapin 2012).…”
Section: Voting In the Westminster Systemsmentioning
confidence: 99%
“…Empirically, and in accordance with the strategic approach to parliamentary behaviour, this literature (Burden, 2007;Bäck et al, 2014;Baumann et al, 2015) arrives at the conclusion that parliamentarians have strong incentives to align their behaviour with the prevailing preferences in their constituencies, which thus maximises their chance of re-nomination and re-election. These results stem -again in accordance with the strategic approach discussed above -to a large extent from connections between representatives and their local voters.…”
Section: Theoretical Frameworkmentioning
confidence: 85%